Isolation and in silico analysis of phosphoenolpyruvate carboxylase gene and effects of indoleacetic acid and kinetin on sucrose production of sugarcane (Saccharum officinarum L.) - Alwash, Noor Faris Hassan (2014)
Sugar is the most important food constituent in almost all countries around the world. The sugarcane plant is the most important source of sugar production in which 80% of the sugar production worldwide is derived from. This study aims to isolate, identify and characterize the phosphoenolpyruvate carboxylase gene (PEPcase) and finding out the effects of indoleacetic acid and kinetin hormones on glucose productivity of sugarcane. Moreover, various bioinformatics tools have been applied to further characterize the PEPcase protein. Three sugarcane cultivars, Tebu Hijau-GG (green stem, green leaf), Tebu Gula-RG (red stem, green leaf) and Tebu Gagak-RR (red stem, red leaf) were used to isolate the PEPcase gene GG-PEPcase, RG-PEPcase and RR-PEPcase respectively. Conserved regions have been detected such as protein active sites, and the phylogenetic tree has been constructed. Furthermore, the 3D protein structure (with predicting the ligand binding sites) has been modeled for these isolated PEPcase genes. In this study, tissue culture technique was used to propagate the plant and the effect of plant growth regulators on sugar content was determined. Twenty culture media have been prepared from different compositions and concentrations of plant hormones to propagate the three sugarcane cultivars and used them to find out the fastest and the healthiest growing plant. The best growing plant was the one that was tissue cultured in media containing (5mg/l) Indole-3-acetic acid (IAA) and (2mg/l) Kinetin (Kin). The juvenile plants were harvested and used to measure the sugar content. The concentrations of sugar were found 10% higher in GG, 24% in RR and 43% in RG than the original plant. Significant increase in sugar production has been detected in all of the three cultivars, and the highest increase has been found in the RG sugarcane cultivars. This may occur because of differences among these cultivars at the genetic level and protein level. This study also showed that RG cultivars are more responsive to the hormone treatments than the other cultivars.